ijee 2023
DOI: 10.48165/ijee.2023.59120
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Educational Module on Diet and Nutrition: A Farm Women Perspective from Aspirational Districts

Abstract: Farm women, although they play a significant role in food and nutritional security of their households, are very much deprived of knowledge and information on food and nutrition. Only few studies have focused on nutrition of farm women and no studies have been found on farm women in aspirational districts in particular. Hence, in the present cross sectional study conducted in 2021, an educational module (folder) entitled “Diet and Nutrition of Farm Women: A Short Guide” was developed in Tamil, Malayalam and En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Hence from the results, it could be concluded that majority of farm women and men belonged to middle age group. The above findings were in consonance with the findings of Vishwanath et al (2021) [16] and Dominic et al (2023) [3]…”
Section: Resultssupporting
confidence: 92%
“…Hence from the results, it could be concluded that majority of farm women and men belonged to middle age group. The above findings were in consonance with the findings of Vishwanath et al (2021) [16] and Dominic et al (2023) [3]…”
Section: Resultssupporting
confidence: 92%
“…Previous study also revealed that only 13 per cent of young farmers were using print for receiving agricultural information (Singh et al, 2021) and the farm periodicals need to be designed according to the personal and social needs of the readers (Nain, 2003). Further, the knowledge level of paddy farmers enhanced by 15 per cent through extension literature similar to that of Monikha et al, (2021), Additionally, Dominic et al, (2023) was in view that educational module (folder) was effective when it was developed keeping in the view content relevancy and quality of the module. Nain et al, (2019) opined that strength of relevance of information and need for agri enterprise creation was major concern for designing the entrepreneurial *Farmers were receiving agricultural information from the sources available in their information environment, FS=Farm School, CWM= Community Wall Magazine technical information packages (ETIPs).…”
Section: General Profile Of the Farmersmentioning
confidence: 61%
“…These districts were selected based on their poor performance across various development indicators, including health, education, nutrition, and basic infrastructure [ 37 , 38 ]. Earlier research conducted in the Aspirational Districts predominantly focused on socioeconomic status, maternal and child health and the effectiveness of education, with no research specifically addressing anaemia which is a critical health issue prevalent among WRA [ 39 43 ]. By examining the prevalence of anaemia in Aspirational Districts, the research aims to inform targeted interventions aimed at reducing anaemia rates and improving the well-being of WRA in these districts.…”
Section: Introductionmentioning
confidence: 99%